ANALISIS LEGAL-SOSIAL TERHADAP KONDISI KESETARAAN DAN KEADILAN GENDER DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN INDONESIA - Indra - Kusumawardhana (Populis : Jurnal Sosial dan Humaniora, 2018)
Undeniably the issue of gender has become a very important issue globally. This urgency surfaced with the inclusion of gender issues as one of the main goals of the transformation of the global collective step, namely Sustainable Development Goals (SDGs) in 2015, which became a clear evidence of the growing concern of the world community regarding gender equality and polemics (un.org). However, gender equality and justice polemics remain a task far from over for Indonesia, especially when referring to the fact that the role of women in Indonesia still shows various inequalities in their correlation with development holistically. This condition is inseparable from the fact that until now Indonesia does not have a law that comprehensively accommodates the protection of women's rights from forms of discrimination against women, and violations of women's human rights in Indonesia's development. In this context, this study is woven within the framework of the urgency of gender equality and justice in Indonesia's development which demands laws that can become a comprehensive legal umbrella for the implementation of gender equality and justice. Using the approach of the social system, gender, and various concepts available in understanding women and development; and using qualitative methodologies in analyzing problems. This study will carry out a social-legal analysis of the implementation of gender equality and justice in order to explain a condition that ultimately shows the urgency of the Gender Equality and Justice Act as a basis for consolidating all elements of society in Indonesia's development today and in the future. Keywords: Legal-Social Analysis, Gender Equality and Justice, Sustainable Development